If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3(x + -8) + -5 = 9(x + 2) * 11 Reorder the terms: -3(-8 + x) + -5 = 9(x + 2) * 11 (-8 * -3 + x * -3) + -5 = 9(x + 2) * 11 (24 + -3x) + -5 = 9(x + 2) * 11 Reorder the terms: 24 + -5 + -3x = 9(x + 2) * 11 Combine like terms: 24 + -5 = 19 19 + -3x = 9(x + 2) * 11 Reorder the terms: 19 + -3x = 9(2 + x) * 11 Reorder the terms for easier multiplication: 19 + -3x = 9 * 11(2 + x) Multiply 9 * 11 19 + -3x = 99(2 + x) 19 + -3x = (2 * 99 + x * 99) 19 + -3x = (198 + 99x) Solving 19 + -3x = 198 + 99x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-99x' to each side of the equation. 19 + -3x + -99x = 198 + 99x + -99x Combine like terms: -3x + -99x = -102x 19 + -102x = 198 + 99x + -99x Combine like terms: 99x + -99x = 0 19 + -102x = 198 + 0 19 + -102x = 198 Add '-19' to each side of the equation. 19 + -19 + -102x = 198 + -19 Combine like terms: 19 + -19 = 0 0 + -102x = 198 + -19 -102x = 198 + -19 Combine like terms: 198 + -19 = 179 -102x = 179 Divide each side by '-102'. x = -1.754901961 Simplifying x = -1.754901961
| 99=-m+8(8+m) | | a/6=6 | | 3z=90 | | y-(-8)=(6/7)(x-5) | | 3x/5-3x/5-7 | | -7.2=1.3n-0.3n-1.0 | | 5(2x+4)+3(2x-2)=24 | | x-.50x=43 | | (y+1)+1=3y | | f-g=3g | | 5(-8b-4)=180 | | 7-(-10+3x)=-238 | | y-(-3)=(8/9)(x-4) | | 2(2-2x)= | | 3x+7=x-21 | | 3x+29-2x+4=-4x | | 2000+9=1000 | | 12ab^2+4ab-16a^3b^2= | | 6(1+6x)=-102 | | -4(u+5)+3u= | | 10d-6=4s-15-3d | | 3(5-4a)=99 | | 6x+5+4x-3=122 | | -92=4(3k-2) | | 8x^2+2x+-15=0 | | z+.625=.9375 | | (x+5)2=108 | | (7+y)(4y+5)=0 | | 20+12x=-128 | | (m^5n^5)^1/6/3(mn)^-1/6 | | 3n=1/81 | | 224=d-12 |